Measuring the embodied waste among industries in Malaysia - Utit, Chakrin; Saari, Mohd Yusof; Hassan, Azman; Tengku Ismail, Tengku Hanidza (Elsevier, 2015)
Recycling is as an alternative solution in reducing the amount of waste generated through production activities. However, the precise level of waste embodiment in each of the industry is unknown. The input-output analysis is applied using the Malaysian input-output table 2010, consisting of 124 industries. The Hypothetical Extraction Method (HEM) is used to extract the waste industry which is identified as sewerage, waste collection and remediation activities. With the extraction, the changes of total output and value added in each 124 industries are recorded and disaggregated into direct and indirect changes. This study reveals that the embodiment level is the highest in wholesale and retail trade industry.